Radiation electron trajectory modulated DC surface flashover of polyimide in vacuum. (19th May 2022) - Wang, Xiaoping; Zheng, Shusai; Li, Zhen; Pan, Shaoming; Fan, Weibo; Min, Daomin; Li, Shengtao
Abstract: Improving surface flashover voltage on vacuum-dielectric interface irradiated by electrons is a long-standing challenge for developing high-voltage and high-power spacecraft technology. The basic issue is understanding the role of radiation electrons in the process of surface flashover. In this paper, a 'three-segment' curve concerning the surface flashover properties under electron irradiation is discovered experimentally. As the gap distance of electrodes increase, the surface flashover voltage of polyimide during electron irradiation presents a trend of firstly increasing, then decreasing, and finally stabilizing. According to the simulation of the trajectory distribution for kinetic electrons, this trend is found to correspond with three typical stages respectively. In stage A, the kinetic electrons are completely deflected and the varying electrode parameters mainly affect the electric field distribution. In stage B, the kinetic electrons can irradiate the part of polyimide. The promoting effect of those electrons on flashover process enhance with the enlargement of the irradiated region. In stage C, trajectories are no longer seriously deflected and the role of kinetic electrons do not vary with electrode parameters. Combining with the results above, a model with combined effects of both kinetic and deposited electrons on surface flashover in vacuum is thus proposed, base on which the guidance for the methods of improving surface flashover voltage during electron irradiation is provided.